Kualitas Produk, Kualitas Pelayanan dan Lokasi terhadap Keputusan Pembelian di Gramedia Mall Central Park - Arip Priyadi; Christine C. Widayati; Didin Hikmah Perkasa; Muhammad Al Faruq Abdullah; Muhamad Ekhsan (IPM2KPE, 2024)
This research aims to evaluate retail performance using sales turnover as a benchmark, with a focus on Gramedia Mall Central Park, which is part of the Gramedia Store network. This research also aims to determine the influence of the variables studied, namely product quality, service quality and location on purchasing decisions. The research design uses a causal quantitative method using an instrument in the form of a questionnaire. This questionnaire was distributed to 105 respondents to obtain more accurate data analysis results. Data analysis was carried out using Smart-PLS (Partial Least Square) through testing the outer model, inner model and hypothesis testing. The research results show that product quality has a significant influence on purchasing decisions, as does service quality and location. The conclusion is that retail performance, especially Gramedia Mall Central Park, can be assessed from the development of sales turnover. Additionally, product quality, service quality, and location play an important role in shaping customer purchasing decisions. Therefore, attention to these factors can improve overall retail performance. Keywords: Product Quality, Service Quality, Purchasing Decisions, Location